Progress in Developing Novel Double-Shell Metal Targets Via Magnetron Sputtering. (3rd April 2018) - Xu, H.; Huang, H.; Walker, J.; Kong, C.; Rice, N. G.; Mauldin, M. P.; Vocke, J. D.; Bae, J. H.; Sweet, W.; Elsner, F. H.; Farrell, M. P.; Wang, Y. M.; et al.
Abstract: Double-shell inertial confinement fusion targets represent a unique platform for achieving ignition. They consist of a low-Z outer ablator, a high-Z inner pusher layer, and a low-density foam layer sandwiched in between. There is the possibility that double-shell targets may achieve ignition at lower ion temperatures due to the containment of radiation and conduction losses as well as requiring smaller convergence ratios. We have explored using magnetron sputtering to make the inner high-Z pusher layers and have demonstrated a W-Cr bilayer inner-shell design. An Al-Be mixture was explored as one of the outer ablator materials. This material takes advantage of Al X-ray M-band absorption to reduce preheating and still retain Be high-ablation speeds. Typical commercial Al-Be materials suffer from phase separation. However, by using magnetron sputtering we have been able to demonstrate homogeneous Al-Be ablator coatings. The sputtered material forms with nanosized grains and has demonstrated excellent machinability. As a second type of shell explored, pushered single shells can exploit large density gradients to stabilize Rayleigh-Taylor instabilities during compression. Sharp gradients will have higher ignition yields and larger grading lengths will be more stable. We were able to demonstrate pushered single shells made from W-Be gradient layers with various grading slopes and provide simulated results showing that the grading profiles can be influenced by the coating rates of two components.